Fifty Consecutive Hemispherectomies: Outcomes, Evolution of Technique, Complications, and Lessons Learned. Issue 2 (30th October 2013) - Lew, Sean M.; Koop, Jennifer I.; Mueller, Wade M.; Matthews, Anne E.; Mallonee, Julianne C.
Abstract: BACKGROUND: Techniques for achieving hemispheric disconnection in patients with epilepsy continue to evolve. OBJECTIVE: To review the outcomes of the first 50 hemispherectomy surgeries performed by a single surgeon with an emphasis on outcomes, complications, and how these results led to changes in practice. METHODS: The first 50 hemispherectomy cases performed by the lead author were identified from a prospectively maintained database. Patient demographics, surgical details, clinical outcomes, and complications were critically reviewed. RESULTS: From 2004 to 2012, 50 patients underwent hemispherectomy surgery (mean follow-up time, 3.5 years). Modified lateral hemispherotomy became the preferred technique and was performed on 44 patients. Forty patients (80%) achieved complete seizure freedom (Engel I). Presurgical and postsurgical neuropsychological evaluations demonstrated cognitive stability. Two cases were performed for palliation only. Previous hemispherectomy surgery was associated with worsened seizure outcome (2 of 6 seizure free; P .005). The use of Avitene was associated with a higher incidence of postoperative hydrocephalus (56% vs 18%; P = .03). In modified lateral hemispherotomy patients without the use of Avitene, the incidence of hydrocephalus was 13%. Complications included infection (n = 3), incomplete disconnection requiring reoperation (n = 1), reversible ischemic neurological deficit (n = 1), and craniosynostosis (n = 1). There were no (unanticipated) permanent neurological deficits or deaths. Minor technique modifications were made in response to specific complications. CONCLUSION: The modified lateral hemispherotomy is effective and safe for both initial and revision hemispherectomy surgery. Avitene use appears to result in a greater incidence of postoperative hydrocephalus.